Transfer danych kosztowych z systemu finansowo-księgowego na potrzeb budżetowania z wykorzystaniem MS Excela - Kes, Zdzisław (Transfer of Cost Data from Accounting's It System to Budgetting by MS Excel, 2007)
The article describes the questions of using imputed sheets of MS Excel in budgeting aiding. The author has concentrated on the estimation of period of budgeting by MS Excel. The article also shows a practical example of MS Excel application for the transfer of cost data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 246-256